Handbook of carbon offset programs trading systems, funds, protocols and standards - Kollmuss, Anja (Environmental market insights., 2010)
Greenhouse gas (GHG) offsets have long been promoted as an important element of a comprehensive climate policy approach. Offset programs can reduce the overall cost of achieving a given emission goal by enabling emission reductions to occur where costs are lower. Offsets have the potential to deliver sustainability co-benefits, through technology development and transfer. They can also develop human and institutional capacity for reducing emissions in sectors and locations not included in a cap and trade or a mandatory government policy. However, offsets can pose a risk to the environmental in.